2021
DOI: 10.1159/000511680
|View full text |Cite
|
Sign up to set email alerts
|

Hollow Fiber and Nanofiber Membranes in Bioartificial Liver and Neuronal Tissue Engineering

Abstract: To date, the creation of biomimetic devices for the regeneration and repair of injured or diseased tissues and organs remains a crucial challenge in tissue engineering. Membrane technology offers advanced approaches to realize multifunctional tools with permissive environments well-controlled at molecular level for the development of functional tissues and organs. Membranes in fiber configuration with precisely controlled, tunable topography, and physical, biochemical, and mechanical cues, can direct and contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 141 publications
0
22
0
Order By: Relevance
“…Other less commonly used routes for fabricating alginate nanofibers by electrospinning include incorporation of co-solvent systems (e.g., glycerol and water), which also improve alginate electrospinnability ( Nie et al, 2008 ), as well as using carrier polymers with co-solvents and surfactants (e.g., DMSO and Triton, respectively) ( Saquing et al, 2013 ) in order to increase the content of alginate and to promote the formation of a 3D network of nanofibers, which may result from the reduction of the surface tension present at high alginate content ( Bonino et al, 2011 ; Velasco-Barraza et al, 2018 ). Owing to their highly porous structure and large specific surface area, alginate nanofibers mimic the extracellular matrix and enhance the proliferation of epithelial cells and the formation of new tissues ( Sun and Tan, 2013 ; Morelli et al, 2021 ). Also, their nano-size and nanofibrous mesh structure enhance hemostasis of injured tissues and stimulate rapid fluid absorption.…”
Section: Alginate Nanoformulationsmentioning
confidence: 99%
“…Other less commonly used routes for fabricating alginate nanofibers by electrospinning include incorporation of co-solvent systems (e.g., glycerol and water), which also improve alginate electrospinnability ( Nie et al, 2008 ), as well as using carrier polymers with co-solvents and surfactants (e.g., DMSO and Triton, respectively) ( Saquing et al, 2013 ) in order to increase the content of alginate and to promote the formation of a 3D network of nanofibers, which may result from the reduction of the surface tension present at high alginate content ( Bonino et al, 2011 ; Velasco-Barraza et al, 2018 ). Owing to their highly porous structure and large specific surface area, alginate nanofibers mimic the extracellular matrix and enhance the proliferation of epithelial cells and the formation of new tissues ( Sun and Tan, 2013 ; Morelli et al, 2021 ). Also, their nano-size and nanofibrous mesh structure enhance hemostasis of injured tissues and stimulate rapid fluid absorption.…”
Section: Alginate Nanoformulationsmentioning
confidence: 99%
“…Lastly, the CNR Institute on Membrane Technology (CNR-ITM, Cosenza) has worked on 3D culture for liver regeneration and neuroregenerative biomaterials [ 87 , 88 , 89 ]. This team investigated artificial 3D membranes for the development of biomimetic models, reliable tools for in vitro observations of neurological diseases [ 90 ]. In the last decade, several membrane bioreactors for neural differentiation have been developed including, PCL and chitosan for neural spheroids growth, PLLA microtube arrays and PLGA membrane platforms [ 91 , 92 , 93 , 94 , 95 ].…”
Section: Application Fieldsmentioning
confidence: 99%
“…Although there are intensive R&D efforts towards nanofiber translation, scale-up of fabrication methods is usually the bottle neck of the process [ 5 ]. While several clinical trials of NF formulations have concluded or are currently recruiting or undergoing, there is a limited number of NF products in clinical use [ 6 , 7 ]. Currently, nanofiber-based products used in medicine field involve filtering devices, surgical implants and wound dressings and patches developed for drug delivery [ 5 ].…”
Section: Introductionmentioning
confidence: 99%